Implementation Model of Integrated Industrial Estate Development Policy for Tukak Sadai Port in South Bangka Regency, Bangka Belitung Islands Province, Indonesia - Justiar Noer; Khasan Effendy; Ngadisah; Sampara Lukman (International Journal of Science and Society, 2020)
The purpose of this study was to find a model for implementing the policy of developing the Integrated Industrial Estate off the Tukak Sadai Port in the South Bangka Regency, Bangka Belitung Islands Province. This research uses qualitative methods with data collection techniques such as observation, in-depth interviews, and literature studies. Data analysis was performed using triangulation techniques. The results found that the model of policy implementation needed to implement the policy of developing the Tukak Sadai Port IIE in the South Bangka Regency, Bangka Belitung Province was to include political, economic, social, and technological factors in Grindle's implementation theory (1980).